Edukasi dan Pelatihan Proteksi Diri saat Adaptasi Kebiasaan Baru dengan ‘PANDAKU’ pada Pekerja Kantin Rumah Sakit di Jakarta - Magdalena Juliani Hardja Buntara; Didi Nugroho; Rr Asyurati Asia; Selviana Wulansari; Laurencia Angelina; Levina Handayani Wibowo; Cathrine Rahayu; Charyne Allika Savitri; Della Puspita Arini (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2022)
'PANDAKU' is a term of make sure to keep your distance, don't wash your hands, discipline to wear a mask, let's vaccinate, gargle and brush your teeth in Bahasa Indonesia. 'PANDAKU' are things that need to be done in adapting new habits during the COVID-19 pandemic. Warehouse workers in hospitals as part of health care institutions are at risk of contracting the virus, so they need to protect themselves from exposure to the virus so that health protocols are implemented properly. Carry out activities boldly using the zoom application. There were 23 participants who were part of the community of hospital canteen workers in Jakarta. Activities carried out in the form of providing education, video demonstrations, and Q&A sessions with the experts. Evaluation of activity participants was carried out by giving pre-test and post-test. Regular activities during a pandemic can be carried out and adapted to the development of the existing pandemic and can be carried out in various different communities.